Effect of vitamin D supplementation on selected inflammatory biomarkers in older adults: a secondary analysis of data from a randomised, placebo-controlled trial. Issue 5 (24th July 2015) - Waterhouse, Mary; Tran, Bich; Ebeling, Peter R.; English, Dallas R.; Lucas, Robyn M.; Venn, Alison J.; Webb, Penelope M.; Whiteman, David C.; Neale, Rachel E.
Abstract: Observational studies have suggested that 25-hydroxyvitamin D (25(OH)D) levels are associated with inflammatory markers. Most trials reporting significant associations between vitamin D intake and inflammatory markers used specific patient groups. Thus, we aimed to determine the effect of supplementary vitamin D using secondary data from a population-based, randomised, placebo-controlled, double-blind trial (Pilot D-Health trial 2010/0423). Participants were 60- to 84-year-old residents of one of the four eastern states of Australia. They were randomly selected from the electoral roll and were randomised to one of three trial arms: placebo ( n 214), 750 μg ( n 215) or 1500 μg ( n 215) vitamin D3, each taken once per month for 12 months. Post-intervention blood samples for the analysis of C-reactive protein (CRP), IL-6, IL-10, leptin and adiponectin levels were available for 613 participants. Associations between intervention group and biomarker levels were evaluated using quantile regression. There were no statistically significant differences in distributions of CRP, leptin, adiponectin, leptin:adiponectin ratio or IL-10 levels between the placebo group and either supplemented group. The 75th percentile IL-6 level was 2·8 pg/ml higher (95 % CI 0·4, 5·8 pg/ml) in the 1500 μg group than in the placebo group (75th percentiles:11·0 v . 8·2 pg/ml), with a somewhat smaller, non-significant difference in 75th percentiles between the 750 μg and placebo groups. Despite large differences in serum 25(OH)D levels between the three groups after 12 months of supplementation, we found little evidence of an effect of vitamin D supplementation on cytokine or adipokine levels, with the possible exception of IL-6.